1999
DOI: 10.1023/a:1007673318947
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A Computerised Mapping Programme (CMP) was created step by step to cover all the needs of a cross sectional population survey conducted in eight villages of Fokida, a rural area of central Greece. The maps of Greece (boundary) and the topographical maps of the eight villages were created using the CMP. A volunteer sample of 1121 out of 2607 inhabitants of the study area participated in the population survey. The participants were tested for brucellosis using serological tests (ELISA and Rose Bengal) and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Using non-pasteurized milk with 21.5% and non-pasteurized cheese with 19.4% had the greatest role in brucellosis incidence. Similarly, in another studies carried out in Khorasan Razavi, it was reported that non-pasteurized milk and cheese can cause brucellosis more than any other dairy products ( 19 ).…”
Section: Discussionmentioning
confidence: 89%
“…Using non-pasteurized milk with 21.5% and non-pasteurized cheese with 19.4% had the greatest role in brucellosis incidence. Similarly, in another studies carried out in Khorasan Razavi, it was reported that non-pasteurized milk and cheese can cause brucellosis more than any other dairy products ( 19 ).…”
Section: Discussionmentioning
confidence: 89%
“…The results of a study conducted in Oman revealed that consuming infected milk and contact with infected cattle were the main causes of Malta fever [73] . In a study on inhabitants of eight villages in Greece, it was demonstrated that using unpasteurized dairy products, being in the risky occupation group (i.e., ranchers and slaughterhouse workers), and having contact with infected animals were among the factors leading to more cases of Malta fever [74] . A study carried out in Northern Egypt reported that people who had contact with animals were more susceptible to Malta fever than those with no animal contact [70] .…”
Section: Discussionmentioning
confidence: 99%